High performance flexible visible-blind ultraviolet photodetectors with two dimensional electron gas based on unconventional release strategy - Zhang, Yi-Yu (2022)
Interdigitated photodetectors (IPDs) based on the two-dimensional electron gas (2DEG) at the AlGaN/GaN interface have gained prominence as high sensitivity ultraviolet (UV) PDs due to their excellent optoelectronic performance. However, most 2DEG-IPDs have been built on rigid substrates, thus limiting the use of 2DEG-IPDs in flexible and wearable applications. In this paper, we have demonstrated high performance flexible AlGaN/GaN 2DEG-IPDs using AlGaN/GaN 2DEG heterostructure membranes created from 8 in. AlGaN/GaN on insulator (AlGaN/GaNOI) substrates. The interdigitated AlGaN/GaN heterostructure has been engineered to reduce dark current by disconnecting the conductive channel at the heterostructure interface. Photocurrent has been also boosted by the escaped carriers from the 2DEG layer. Therefore, the utilization of a 2DEG layer in transferrable AlGaN/GaN heterostructure membranes offers great promises for high performance flexible 2DEG-IPDs for advanced UV detection systems that are critically important in myriad biomedical and environmental applications.